Elucidating drought responsive networks in tef (Eragrostis tef) using phenomic and metabolomic approaches. Issue 1 (22nd December 2021) - Girija, Aiswarya; Han, Jiwan; Corke, Fiona; Brook, Jason; Doonan, John; Yadav, Rattan; Jifar, Habte; Mur, Luis A. J.
Abstract: Drought is a major abiotic stress that limits crop productivity and is driving the need to introduce new tolerant crops with better economic yield. Tef ( Eragrostis tef ) is a neglected (orphan) Ethiopian warm‐season annual gluten‐free cereal with high nutritional and health benefits. Further, tef is resilient to environmental challenges such as drought, but the adaptive mechanisms remain poorly understood. In this study, metabolic changes associated with drought response in 11 tef accessions were identified using phenomic and metabolomic approaches under controlled conditions. Computerized image analysis of droughted plants indicated reductions in leaf area and green pigments compared with controls. Metabolite profiling based on flow‐infusion electrospray–high‐resolution mass spectroscopy (FIE‐HRMS) showed drought associated changes in flavonoid, phenylpropanoid biosynthesis, sugar metabolism, valine, leucine and isoleucine biosynthesis, and pentose phosphate pathways. Flavonoid associated metabolites and TCA intermediates were lower in the drought group, whereas most of the stress‐responsive amino acids and sugars were elevated. Interestingly, after drought treatment, one accession Enatite (Ent) exhibited a significantly higher plant area than the others, and greater accumulation of flavonoids, amino acids (serine and glycine), sugars (ribose, myo‐inositol), and fatty acids. The increased accumulation of these metabolites could explain the increased tolerance to drought in Ent compared with other accessions. This is the first time a non‐targeted metabolomics approach has been applied in tef, and our results provide a framework for a better understanding of the tef metabolome during drought stress that will help to identify traits to improve this understudied potential crop.